Effectiveness of Hybrid Discovery Learning in Enhancing Students’ Comprehension and Critical Thinking Skills - Nadjamuddin, Lukman; Rore, Idrus; Mahmud, Jamaludin; Zaky, Muhammad; Tadeko, Nurgan; Nirmala, Besse (International Journal of Interactive Mobile Technologies (iJIM), 2026)
This study sought to explore how the hybrid discovery learning (HDL) model can support and enhance students’ comprehending of the material. In particular, it examined the differences in learning outcomes when the HDL approach was implemented with and without the support of a learning management system (LMS). A quasi-experimental design with a descriptive quantitative approach was employed, involving three cohorts: two control cohorts and one experimental cohort. Data were gathered through an assessment of students’ critical thinking skills in a secondary school history class. The results indicated that both forms of the HDL model, whether implemented in a conventional setting or supported by an LMS, contributed significantly to enhancing students’ comprehension. The experimental cohort and Control cohort 2 outperformed Control cohort 1, which was taught using the direct instruction model. However, LMS integration did not yield significant additional benefits. These findings affirm the effectiveness of the HDL model in improving student learning outcomes and offer meaningful insights that can inform the design and implementation of more impactful active learning strategies in the future.